Development of a Mobile Application to Improve Digital Literacy Skills - Muh. Aldinova Setiawan; Bayu Wibisana; Hendri Purnomo (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2025)
The rapid advancement of digital technologies in recent years has created an urgent need to improve digital literacy skills, especially among students and young adults who are active users of mobile devices and online platforms. This study aims to develop a mobile application designed to improve users’ digital literacy skills, with a particular focus on accessing, evaluating, and using digital information responsibly. The study followed a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model to systematically guide the creation and testing of the application. The mobile application includes interactive learning materials, quizzes, and simulations covering core aspects of digital literacy such as information seeking strategies, critical evaluation of online sources, digital security practices, and ethical behavior in digital environments. Initial testing with a sample group of students showed significant improvements in digital literacy competencies, as evidenced by an increase in post-test scores compared to pre-test results. User feedback also highlighted the application’s ease of use, engaging interface, and relevance to real-world digital challenges. The study concludes that the mobile application can serve as an effective educational tool in promoting digital literacy, offering flexible and accessible learning opportunities that align with the digital habits of modern learners.